2009
DOI: 10.1007/s10689-009-9287-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of germ-line TP53 mutations in women diagnosed with breast cancer before age 30

Abstract: Germ-line mutations in the TP53 gene are rare, but predispose women to a range of cancer types, including early-onset breast cancer. Breast cancers in women from families with the Li-Fraumeni syndrome often occur before age 30. The prevalence of deleterious TP53 mutations in unselected women with early-onset breast cancer is not precisely known. If mutations were found to be sufficiently common, it might be prudent to offer genetic testing to affected women in this age group. We screened the entire TP53 gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…Breast cancer at young age was not included in the 2009 revised Chompret criteria because they concluded that the mutation detection rate for patients with early onset breast cancer without a family history of cancer or multiple primary tumours was <5% 7. Ginsburg et al did not find any TP53 mutations in 95 sporadic breast cancer cases under 30 years of age 28. Testing adrenal cortical carcinoma patients for germline TP53 mutations revealed a 50–97% chance of finding a mutation 29–32.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer at young age was not included in the 2009 revised Chompret criteria because they concluded that the mutation detection rate for patients with early onset breast cancer without a family history of cancer or multiple primary tumours was <5% 7. Ginsburg et al did not find any TP53 mutations in 95 sporadic breast cancer cases under 30 years of age 28. Testing adrenal cortical carcinoma patients for germline TP53 mutations revealed a 50–97% chance of finding a mutation 29–32.…”
Section: Discussionmentioning
confidence: 99%
“…Mean age at first cancer diagnosis among females heterozygous for a germline TP53 mutation in one prospective cohort was 29 years [9]. The reported frequency of germline TP53 mutations in population-based series of women diagnosed with unselected invasive breast cancer before age 30 years ranges from <1% to 4% [5, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of TP53 mutations ranging from less than 1 to 5% has been reported in studies conducted in Caucasian populations [15][16][17][18][19][20][21][22][23][24]. Few data exist on the contribution of TP53 to early-onset breast cancer in Non-Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%